Strategy of the improvement of the training-teaching process - Yusifova, Naila (Dunakavics, 2024)
At the first stage (1999), organizational work has been done to create a normative legal economic and information base of the new education system that meets the modern requirements, ensuring citizens’ right to education. Establishment of organizational, legal, regulatory, personnel, financial, logistical, scientific, educational and methodological and information support for the solution of the problems that provide for socio-economic stability of the education sector and the implementation of large-scale reforms in the second stage covering short-term prospective; the management model is expected to be created. The third stage is the implementation mechanism of all other measures envisaged by the Program. The effectiveness of the use of new methods in the training depends primarily on the organizational and training of teacher training. Improving the quality of education has influenced the substance of the subject and object concept in the learning process and led to a new sense of co-operation. The active training in the pedagogical process is one of the objectives of educational reform. These methods, which create the conditions for improving the quality of the training, should first be mastered by teachers. Active learners are learning guides and learners as researchers. The quality of the mentioned technology is accompanied by intensification of thinking activity.